Modern View on the Etiopatogenesis of Chronic Recurrent Aphthosis Stomatitis - Rasulova Mohigul Matyakubovna (Genius Journals, 2022)
Recently, there has been an increase in the number of patients with chronic recurrent aphthous stomatitis. Due to the unclear etiology of the disease, the issue of diagnosing aphthous stomatitis remains relevant for dentists. The article presents a review of the literature on the etiological factors and pathogenesis of chronic recurrent aphthous stomatitis
Keywords: chronic recurrent; aphthous stomatitis; etiology; pathogenesis